A novel smartphone application for bladder cancer management (BCM App): Design, development, and usability evaluation - Atefeh Khosrobeigi; Mehrdad M. Sichani; Fatemeh Rangraz-Jeddi; D Davoud Gharakhani; Elham Mousavinasab; Shima Anvari; Hosein Akbari; Farhad Fatehi; Ehsan Nabovati (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Providing clinical guidelines to clinicians using innovative technologies seems practical and useful. This study aimed to design, develop, and evaluate a smartphone application to assist urologists in managing bladder cancer (BCM App). MATERIALS AND METHODS: The study was conducted in three phases, following the user-centered design model, at the urology clinic of Khorshid Hospital (Isfahan, Iran) in 2021. Components and functionalities for BCM App were specified in three focus group sessions with urologists and urology residents using clinical guidelines. Adopting the Delphi technique, the participants completed a questionnaire addressing issues including educating and informing clinicians, performing clinical calculations, representing graphical information, and recording patient information. A conceptual model for the app was designed, and the final product was developed. The usability of the BCM App was evaluated using the think-aloud technique by usability experts and end-users. RESULTS: The app's components were categorized into three groups: Patient evaluation, disease staging and management, and patient follow-up. The app's main components included "bladder cancer classification," "disease grading and staging," "management based on the disease stages," "principles of intravesical treatment," and "classifying follow-ups by disease stages." Moreover, the most prominent app's functionalities were "using staging and grading table," "using American Urological Association risk stratification," "calculating disease stages," "calculating patient's follow-up," and "recording patient information." The usability evaluation results revealed that the BCM App was at a "highly acceptable" level. CONCLUSION: To design and develop a smartphone app for managing bladder cancer, the involvement of urologists is crucial. Apart from assisting urologists in effectively managing bladder cancer, the proposed app has the potential to enhance residents' knowledge and streamline their access to evidence.